2019
DOI: 10.1057/s41270-019-00063-6
|View full text |Cite
|
Sign up to set email alerts
|

Customer relationship management technology: bridging the gap between marketing education and practice

Abstract: The recent machine learning and analytics advances in customer relationship management (CRM) technologies place new demands on marketing education and practitioners to develop the skills needed to use the technology. Compounding the issue, research on the use of technology in sales curriculum is underdeveloped. In a comprehensive review of the sales education literature, one study identified that only six articles on sales technology were published in major marketing education journals from 1979 to 2013. In an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 89 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…Limited studies explore the impact of exposure to sales technology in the classroom on student development and job performance. One exception is Harrison and Ajjan’s (2019) study of CRM technologies in marketing education and practice. These authors found that students’ who have experience with advanced CRM technologies are more competitive in the job market.…”
Section: Discussion Of General Resultsmentioning
confidence: 99%
“…Limited studies explore the impact of exposure to sales technology in the classroom on student development and job performance. One exception is Harrison and Ajjan’s (2019) study of CRM technologies in marketing education and practice. These authors found that students’ who have experience with advanced CRM technologies are more competitive in the job market.…”
Section: Discussion Of General Resultsmentioning
confidence: 99%
“…As language models become prevalent, students will encounter them frequently, directly or through search engines like Bing, Google and Brave (Harrison & Ajjan, 2019). Language models can generate assessed work in a human-like manner (Dwivedi et al, 2023;Farrokhnia et al, 2023).…”
Section: Concerns Of Chatgpt On Students' Over-relyingmentioning
confidence: 99%
“…Language models can generate assessed work in a human‐like manner (Dwivedi et al., 2023; Farrokhnia et al., 2023). The generated text, however, in terms of the knowledge it offers and the accuracy of the knowledge, unless checked, is questionable (Harrison & Ajjan, 2019; Roy & Rambo‐Hernandez, 2021). It is tempting to suggest that language models only be used to develop early drafts and that the output is thoroughly checked (Farrokhnia et al., 2023; Mohdzaini, 2023).…”
Section: Students' Use Of Chatgptmentioning
confidence: 99%
See 1 more Smart Citation
“…The customer data processing evolution is a result of the ICT and online strategies development (Chen, 2017). CRM built its strategies on data analytics results to develop competitive strategies (Harrison, 2019).…”
Section: Crm As Support To E-commercementioning
confidence: 99%